The Impact of Cognitive-Behavioral Intervention (CBI) on Enhancing Mental Health and Quality of Life in Lung Cancer Patients Undergoing Chemotherapy Nursing - Fan M; Wei X (Journal of Multidisciplinary Healthcare)
Miaoxin Fan,* Xiuli Wei* Department of Oncology, Taihe County People’s Hospital, Fuyang, 236699, People’s Republic of China*These authors contributed equally to this workCorrespondence: Miaoxin Fan, Email qnx198@126.comObjective: This study aims to assess the impact of cognitive behavior intervention (CBI) on the mental health and quality of life of patients with lung cancer.Methods: A retrospective study was conducted involving 80 lung cancer patients admitted to Taihe County People’s Hospital between June 2022 and June 2023. Patients were divided into two groups: an experimental group receiving CBI and a comparison group receiving conventional care only, with 40 patients in each group. Mental health was evaluated using the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS). The Simplified Health Survey Scale (SF-36) was utilized to assess overall quality of life across eight dimensions: physical functioning, role limitations due to physical health, bodily pain, general health, vitality, social functioning, role limitations due to emotional problems, and mental health. Additionally, patient satisfaction with nursing care was measured. Demographic characteristics, including age and gender distribution, were recorded for both groups.Results: Baseline characteristics of the total study population (n=80) were documented, including age, sex, and lung cancer stage. The mean age of the participants was 60.16 ± 9.13 years.Keywords: lung cancer, chemotherapy, nursing, cognitive behavior intervention, mental health, quality of life, nursing satisfaction